Diamond nitrogen‐vacancy centres spin‐state‐based quantum sensor using a compact broadband antenna. Issue 24 (21st October 2022) - Cui, Mingming; Shen, Fazhong; Qiao, Yingying; Du, Guanxiang; Zhuo, Xiang; Zang, Jiawei; Zhang, Zhenyuan; Wang, Yi; Li, Lei; Gao, Yang
Abstract: This paper presents a compact broadband antenna that is used in the spin‐state‐based magnetic field quantum sensor. In the diamond nitrogen‐vacancy (NV) centre system, the qubit resonance is excited by the microwave signal, and the frequency shift is proportional to the external magnetic field strength. Conventional narrow‐band antennas or single resonators are not able to match the resonance frequency of the NV centre over a wide bandwidth, resulting in degraded sensitivity and dynamic range of the sensor. Here, the authors designed a compact broadband antenna, which achieves a fractional bandwidth of 71.43% at the Zeeman splitting frequency of 2.87 GHz. With the introduced slot structure on the antenna, a higher microwave near field strength can also be achieved, which improves the magnetic field sensitivity and dynamic range. By applying our design antenna, the experimental results indicate that the NV‐based quantum sensor achieves a sensitivity of 3.07 μT/Hz 1/2 and a dynamic range up to 44.9 dB, which are both greatly improved compared to sensor that uses a conventional antenna.